Designing human-robot collaboration (HRC) workspaces in industrial settings: A systematic literature review. (January 2022) - Simões, Ana Correia; Pinto, Ana; Santos, Joana; Pinheiro, Sofia; Romero, David
Highlights: HRC workstation completely human-centered promotes health, safety and sustainability. Safety and ergonomics principles should be considered in the HRC design. Implementation of HRC in manufacturing implies a multidisciplinary research approach. Future research should support decision-makers about HRC implementation. Abstract: In the pursuit of increasing efficiency, productivity and flexibility at production lines and their corresponding workstations, manufacturing companies have started to heavily invest in "collaborative workspaces" where close interaction between humans and robots promises to lead to these goals that neither can achieve on their own. Therefore, it is necessary to know the contributions, recommendations and guidelines that literature presents in terms of designing a manufacturing workplace where humans and cobots interact with each other to accomplish the defined objectives. These aspects need to be explored in an integrated and multidisciplinary way to maximize human involvement in the decision chain and to promote wellbeing and quality of work. This paper presents a systematic literature review on designing human-robot collaboration (HRC) workspaces for humans and robots in industrial settings. The study involved 252 articles in international journals and conferences proceedings published till 2019. A detailed selection process led to including 65 articles to further analysis. A framework that represents the complexity levels of the influencing factors presented in human-robot interaction (HRI) contexts was developed for the content analysis. Based on this framework the guidelines and recommendations of the analysed articles are presented in three categories: Category 1 – the first level of complexity, which considers only one specific influencing factor in the HRI. This category was split into two: human operator, and technology; Category 2 – the second level of complexity, includes recommendations and guidelines related to human-robot team's performance, and thus several influencing factors are present in the HRI; and, finally, Category 3 – the third level of complexity, where recommendations and guidelines for more complex and holistic approaches in the HRI are presented. The literature offers contributions from several knowledge areas capable to design safe, ergonomic, sustainable, and healthy human-centred workplaces where not only technical but also social and psychophysical aspects of collaboration are considered.